LITERASI INVENTARISASI HAMA DAN PENYAKIT TEMBAKAU DELI DI PERKEBUNAN SUMATERA UTARA - Siregar, Ameilia Zuliyanti (Jurnal Online Pertanian Tropik, 2016)
Tobacco Deli" Sumatra, the belle of the European cigar tobacco is an economically valuable commodity exports as a source of foreign exchange. Deli tobacco leaf wrapper cigar known as the number one in the world, so it is still needed by plants producing high-quality cigars. Approach to literacy method in the inventory of the tobacco plant pest and disease appropriately in order to improve tobacco produktiviats to foreign countries. The main pests of tobacco plants were identified from the source of literacy is Thrips parvispinus, Spodoptera litura, Helicoperva armigera, Myzus persicae, Agrotis ipsilon, Heliothis, Meloydogyinae, Aphis sp, Thrips sp, Bemisia sp. While the types of diseases that often attack the tobacco plant was charred trunks, black shank, homeopathic leaf, spotting coelat, late blight and viruses. Preparation of seed healthy and productive; tillage seeding and planting land; Biological Control Agents consumption (BCA), rice husk ash, ash kitchen, liquid organic fertilizer and weed-free treatment that is an appropriate way to improve the productivity of tobacco as a commodity exporting country Indonesia.